Investigation the Effect of Low, Medium and High Dose of X-Radiation on the Expression of E-cadherin in Colorectal Cancer Cell Line - Sh Soleymanifard; M Rostamyari; F Rassouli; A R Mehdizadeh (Journal of Biomedical Physics and Engineering, 2021)
Background: Radiotherapy has become a part of therapeutic process of more than 50 percent of patients suffering from cancer. However, recent studies have shown that radiation therapy might affect the expression of adhesive molecule related genes such as E-cadherin and cause cancer cells to move and migrate. Besides, various studies have reported that the expression of E-cadherin changes differently after radiation treatment. There are several studies which showed the loss of E-cadherin function after radiation; however, this reduction has not been observed in others. Objective: This study aims to investigate the effect of different radiation doses of X-ray on changes that might occur in the expression of E-cadherin gene in colorectal cancer cell line HT-29.Material and Methods: In this experimental study, the cells cultured in flasks were irradiated with X- rays in different doses, including 0.1, 2.5, 5, and 10 Gy; then, the expression of E-cadherin gene was measured using real-time PCR. Results: The expression of E-cadherin did not change significantly in post-irradiated HT-29 cell line after different radiation doses of X-ray. Conclusion: The results showed that low, medium and high doses of X- radiation did not change the expression of E-cadherin gene in HT-29 cancer cells. However, it has been reported that radiation mostly downregulated the expression of E-cadherin and mediated metastasis formation and invasiveness in different cancer cell lines. Therefore, further studies need to be conducted to investigate the effects of radiation dose on the molecular pathways contributing to regulation of E-cadherin in HT-29 cell line.